Audit Office Reputation Shocks from Gains and Losses of Major Industry Clients - Francis, Jere R.; Mehta, Mihir N.; Zhao, Wanli (Contemporary Accounting Research, 2017)
Abstract Our study reports evidence on the dynamic effects of client switches on auditor reputations and fee premia. Offices of large accounting firms that lose (gain) major industry clients experience a reputation shock leading to more same‐industry client losses (gains) over the next two years. There is also a shift in audit fees charged to other same‐industry clients when a major client loss (gain) results in an audit office losing (gaining) city‐level industry leadership. A major client loss or gain also creates a short‐term capacity shock to an audit office's ability to supply high‐quality audits. However, there is no evidence of reputation spillovers to other‐industry clients in the audit office, or to clients in other offices of the accounting firm.